Encontros entre ficção e não-ficção em A sangue frio, de Truman Capote - Carvalho, Clarissa Patrício (2023)
Since its rise in the 1960s, the New Journalism was regarded as "creative non-fiction". Within the movement, several authors emerged when using journalistic techniques to write literary works. One of them is Truman Capote, who stood out most notably with In cold blood (1966). The main point of this thesis is to discuss the book to show that, despite having clear traces of non-fiction, as determined by the New Journalism and Capote's conceptions about his own work, the presence of fictional traces throughout the narrative is very significant. In order to do so, the characteristics of the movement demonstrated by Tom Wolfe are compared with the fictional theories of Booth, Jauss and Genette, to understand that in Capote's writing, the line between fiction and non-fiction is tenuous